Autotrophic Fixed-Film Systems Treating High Strength Ammonia Wastewater - Aqeel, Hussain; Liss, Steven N. (Frontiers in Microbiology, 2020)
The potential of autotrophic fixed-film and hybrid bioreactors to treat high strength ammonia wastewater (1000 mgN/L) was investigated in this study. Two configurations of fixed-film systems, including moving bed bioreactor (MBBR) and BioCord™, both setup in a sequencing batch reactor (SBR) and continuous stirred tank reactor (CSTR) configuration, were operated for 306 days. The laboratory-scale bioreactors were seeded with activated sludge from a municipal wastewater treatment plant and fed synthetic wastewater with no organics. After a startup time of 45 days, the influent ammonia concentration was gradually increased (10% every five days) from 130 to 1000 mgN/L for the enrichment of nitrifying bacteria and seamless acclimation to high strength ammonia wastewater. Stable ammonia removal was observed up to 750 mgN/L (on day 145) in the MBBR SBR (94-100%) and CSTR (72-100%), and BioCord™ SBR (96-100%) and CSTR (92-100%). Ammonia removal declined to 87% ±6, in all bioreactors treating 1000 mgN/L (on day 185). Following long-term operation at 1000 mgN/L (on day 306), ammonia removal was 93-94% in both the MBBR SBR and BioCord™ CSTR; whereas, ammonia removal was relatively lower in MBBR CSTR (20-35%) and BioCord™ SBR (45-54%). Acclimation to increasing concentrations of ammonia led to the enrichment of nitrifying (Nitrosomonas, Nitrospira, and Nitrobacter) and denitrifying (Comamonas, OLB8, and Rhodanobacter) bacteria (16S rRNA gene sequencing (Illumina)) in all bioreactors. In the hybrid bioreactor, the nitrifying and denitrifying bacteria were relatively more abundant in flocs and biofilms, respectively. The abundance of Nitrosomonas was relatively higher in the microbial communities of the SBRs compared to the CSTRs. Nitrospira and OLB8 were relatively more abundant in microbial communities of MBBR bioreactors; whereas, Rhodanobacter was relatively predominant in BioCord™ bioreactors. The presence of dead cells (in biofilms) suggests that in the absence of an organic substrate, endogenous decay is a likely contributor of nutrients for denitrifying bacteria. Further studies are required to assess the contribution of organic material produced in autotrophic biofilms (by endogenous decay and soluble microbial products) to the overall treatment process. Furthermore, the possibility of sustaining autotrophic nitrogen in high strength waste-streams in the presence of organic substrates warrants further investigation.